Tyler Perry : Interviews - Perry, Tyler (Book collections on Project MUSE., 2019)
A career-spanning collection of interviews with the multimedia phenomenon who has directed groundbreaking films like Diary of a Mad Black Woman that feature mostly African American actors and tell stories about adversity, faith, family, and redemption.